Unfolding Ubiquitin by force: water mediated H-bond destabilization - Pabón, Germán; Departamento de Física Facultad de Ciencias Pontificia Universidad Javeriana (2012)
Using the “pull and wait” (PNW) simulation protocol at 300 K, we studied the unfolding by force of an ubiquitin molecule. PNW was implemented in the CHARMM program using an integration time step of 1 fs and a uniform dielectric constant of 1. The ubiquitin molecule, initially solvated, was put under mechanical stress, exerting forces from different directions. The rupture of five hydrogen bonds between parallel strands β1 and β5 takes place during the extension from 13 to 15 Å, defines a mechanical barrier for unfolding and dominates the point of maximum unfolding force. The simulations described here show that given adequate time, a small applied force can destabilize those five H-bonds relative to the bonds that can be created to water molecules; allowing the formation of stable H-bonds between a single water molecule and the donor and acceptor groups of the interstrand H-bonds. Thus, simulations run with PNW show that the force is not responsible for “ripping apart” the backbone H-bonds; it merely destabilizes them making them less stable than the H-bonds they can make with water. Additional simulations show that the force necessary to destabilize the H-bonds and allow them to be replaced by H-bonds to water molecules depends strongly on the pulling direction. By using a simulation protocol that allows equilibration at each extension we have been able to observe the details of the events leading to the unfolding of ubiquitin by mechanical force.